Спектральні характеристики хвиль, збуджених фазово-модульованим акустичним сигналом у нелінійному геофізичному середовищі - Нагорний, В.П.; Денисюк, І.І.; Юшицина, Я.О. (Геоінформатика, 2014)
Досліджено частоти та амплітуди коливань, що генеруються нелінійним геофізичним середовищем у процесі обробки його фазово-модульованим акустичним сигналом. Результати досліджень можуть бути використані під час акустичної обробки нафтовмісних порід з метою збільшення дебіту видобувних свердловин. Исследованы частоты и амплитуды колебаний, генерируемые нелинейной геофизической средой в процессе обработки ее фазово-модулируемым акустическим сигналом. Результаты исследований могут быть использованы при обработке нефтесодержащих пород с целью увеличения дебита добывающих скважин. It is known from practical experience that wide frequency spectrum of acoustic impulse action makes possible to affect with reasonable effectiveness most structural elements in the layer-fluid system. Different technological methods are used in order to expand spectral characteristics of acoustic impact on geophysical medium of the layer. Among them: biharmonic impact by acoustic waves, amplitude- and phase-modulated acoustic disturbances, etc. However, insufficient attention has been paid to theoretical justification of the methods. The studies of spectral characteristics of phase-modulated acoustic waves during their impact on non-linear geophysical medium were conducted on the basis of heterogeneous wave equation. A method of successive approximations has been used. It has been found that as a result of non-linear effects and interaction of harmonic vibrations in geophysical medium with square and cubic nonlinearities, a wide spectrum of vibrations with amplitudes within the limits of 10⁻⁵–10⁻⁹ m⁻¹ is generated. Wave actions with such amplitudes may serve as a trigger for release of interior energy generated during the process of interaction of harmonic waves with fissures within the medium of a layer. This leads to opening of fissures accompanied by emission of high-frequency waves. In case of high-frequency waves interacting with the fluid layer; its viscosity decreases. At this point, mobility of fluid in filtration channels of the layer and its supply to the well bottom increase. The results of the studies can be used during acoustic processing of oil-bearing rocks to increase the rate of yield of oil and gas wells.